STABILITY STUDY OF OPEN MINE SLOPES AT PIT 22 GN PT KITADIN SITE EMBALUT, KUTAI KARTANEGARA REGENCY, EAST KALIMANTAN PROVINCE - Tandidatu T. Deny; Sundek Hariyadi (Indonesian Mining Journal, 2021)
The stability of slope, both on the slope of work and the final slope, is a very important aspect of slope stability, both on the slope of work and the final slope in open pit mining activities. The inconsistency of the slopes will result in the collapse of rocks around the excavation site. This happens because the condition of the rock when it has not been excavated is generally balanced. However, due to the discontinuous patterns that occur other than naturally and also due to the mining activities such as excavation, blasting and others, cause a reduction in the retaining force of the rock on the slope results in the equilibrium of the force tends to shift and is not balanced. Study of the stability of the open pit highwall slope at PIT 22 GN PT Kitadin Site Embalut, Kutai Kartanegara Regency, East Kalimantan Province was carried out with the aim to know the rock characteristics, to calculate slope geometry stable safety factors, and to recognize the type of landslide using a bishop method. The results of the modeling consist of several heights and slopes, as well as angles that is formed. Section AA’ has a safety factor value of 1.387, section BB has a safety factor of 1.482, section BB' has a safety factor value of 1.390, section DD' has a safety factor value of 1.318, section EE has a safety factor value of 2,381, section FF' has a safety factor value of 2.426, section GG' has a safety factor value of 2.424, section HH 'has a safety factor value of 2.339.